Pengembangan Bina Diri dan Keterampilan Sosial Penyandang Disabilitas Intelektual dan Mental Melalui Program Independent Pilot - Rani Andriani Tunggal; Heni Atika Putri; Jihan Khalisa Salsabila; Nurcahya Priantoro; Santa Veronika Sidauruk; Syaefudin Suminto (Institut Pertanian Bogor, 2025)
There are approximately 22.97 million persons with disabilities in Indonesia, including 7,358 in Bogor Regency, of whom 1,457 have intellectual disabilities and 859 have mental disabilities. Rumah Azaki, a social welfare institution in Bogor Regency, faces challenges in facilitating individuals with disabilities to develop self-care skills and social competencies. The Independent Pilot program was designed to address these issues by enhancing self-care abilities in daily activities, optimizing comprehension of simple instructions, improving cognitive skills, and developing fine motor and social interaction skills through a horticultural therapy approach. The program was implemented in four stages: Problem identification, preparation, implementation, monitoring, and evaluation. The implementation phase consisted of five key activities: independent pilot journeys, acceptance pilots, creativity pilots, hydroponic days, and exhibition pilots. The results demonstrated significant improvements in self-care skills (eating, drinking, and tidying up), cognitive abilities, and understanding of simple instructions through the Independent Island board game, as well as fine motor skills and social interaction through horticultural activities such as planting, maintaining, and harvesting hydroponic plants. Participants with intellectual disabilities showed up to 80% improvement in planting and plant care activities, whereas those with mental disabilities improved by up to 40%. Thus, the Independent Pilot program has proven effective in enhancing the self-development, instruction comprehension, and motor skill proficiency of individuals with disabilities. This success was achieved through close collaboration between academia, the community, the government, and the media. This program can be adapted and implemented in other regions to further support the self-development and social skills of people with disabilities.